Rehabilitation of Degraded Lands in Semiarid and Subhumid Ecologies in India - Singh, Virendra Pal; Verchot, Louis V.; Martius, C.; Nayak, D.; Rizvi, J. (Springer, 2018)
Land degradation is a complex phenomenon caused by natural and anthropogenic factors. These factors create and accelerate soil erosion and contribute to the loss of biodiversity and degradation of soil quality and hydrological features. Adoption of a gamut of appropriate soil and water conservation measures, protection of vegetation from overgrazing, assisted regeneration of vegetation, etc. maybe one of the viable options to protect, rehabilitate, and rejuvenate the degraded lands. This paper presents the results achieved 10 years after the application of these measures in the semiarid (Rajasthan) and subhumid (Odisha) ecologies in India. There were considerable changes and improvements in ecological features in both the ecologies. Reduced level of soil erosion, some increase in soil depth, enhanced vegetation cover, improved vegetation composition and intraspecies density, and hydrological conditions were positively altered. The hydrological changes were visible not only at the study site but also in the villages inhabited in downstream of the study sites, where inhabiting communities claim increased and for longer duration water level in their wells. Due to increased water availability, these communities have successfully ventured in growing more crops, indicating increased cropping intensity on their land.